Very thin thermally stable TiO2 blocking layers with enhanced electron transfer for solar cells. (December 2017) - Kment, Stepan; Krysova, Hana; Hubicka, Zdenek; Kmentova, Hana; Kavan, Ladislav; Zboril, Radek
Graphical abstract: Highlights: TiO2 ultra-thin blocking films were deposited by high-energy magnetron sputtering. The rutile structure was achieved under low temperature (<150 °C) of deposition. Combination of HiPIMS and MF plasma discharges led to highly thermally stable films. TiO2 films showed excellent dual function as blocking and electron transfer layers. Abstract: Very thin TiO2 blocking layers (BLs) are important components for achieving high solar power conversion efficiencies (PCEs) in the dye-sensitized solar cells, and particularly perovskite solar cells (PSCs). When reasonably thin, TiO2 BLs prevent recombination of photogenerated charges at the conductive fluorine-doped tin oxide (FTO) glass substrate used in these devices. However, all previous attempts to generate efficient TiO2 BLs have been hampered by an insufficient charge transfer rate at quasi-amorphous TiO2 and very low thermal stability, leading to the loss of blocking properties after thermal calcination. In this work, we report the deposition of homogenous very thin (∼30 nm) TiO2 BLs by combining advanced high impulse power magnetron sputtering (HiPIMS) and additional bipolar medium-frequency (MF) magnetron co-sputtering. The as-deposited TiO2 films were shown to provide excellent blocking properties which were preserved even after thermal treatment at 450 °C. Moreover, TiO2 BLs thermally treated at 450 °C show a well-developed rutile structure and 70 times higher photocurrents compared to the as-deposited layers. This work opens possibilities for the utilization of very thin TiO2 layers in solar cell technologies providing a double mode of action: blocking functionality and efficient electron transport.